2005
DOI: 10.1152/ajpheart.00511.2004
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of MLCK210 induces subtle changes in vascular reactivity but does not affect cardiac function

Abstract: plays a key role in the regulation of actomyosin contraction in a large variety of cells. Two isoforms have been described: a short isoform, widely expressed in smooth muscle cells; and a long isoform (MLCK210), mainly localized in the endothelium. This study investigated the consequences on different cardiovascular parameters of MLCK210 gene deletion using MLCK210 knockout mice and of pharmacological inhibition of the kinase using a specific MLCK inhibitor. Deletion of MLCK210 did not affect systolic blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…These findings suggested that skeletal muscle MLCK does not play a major role in regulating cardiac MLC2. Similarly, ablation of the long form of smooth muscle MLCK, as described in another recent study, 12 did not affect cardiac function, as determined by systolic blood pressure, heart rate, or echocardiographic measurements. Electrocardiographic analysis showed neither atrio-nor intraventricular conduction or repolarization defects.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…These findings suggested that skeletal muscle MLCK does not play a major role in regulating cardiac MLC2. Similarly, ablation of the long form of smooth muscle MLCK, as described in another recent study, 12 did not affect cardiac function, as determined by systolic blood pressure, heart rate, or echocardiographic measurements. Electrocardiographic analysis showed neither atrio-nor intraventricular conduction or repolarization defects.…”
supporting
confidence: 58%
“…The study, indeed, has identified a new MLCK that is specifically expressed in the heart, although the presence of such a MLCK species is not unreasonable after we have learned from recent knockout studies as described above. 11,12 Kasahara and colleagues identified a rodent MLCK during the process of identifying genes regulated by cardiac homeobox protein Nkx2-5. The identified MLCK, which has been named "cardiac MLCK," as it would be expected, encodes 795 aa with a predicted molecular mass of 86 kDa excluding posttranslational modifications.…”
mentioning
confidence: 99%
“…; Pfizer Santé Animale, Paris, France) and killed by decapitation. Aortae were removed, and the adhering fat and connective tissue were carefully cleaned as described previously (Ralay Ranaivo et al, 2004;Ohlmann et al, 2005). Aortic rings of approximately 2 mm, after incubation in a medium with or without MPs, were mounted on a wire myograph filled with physiological salt solution of the following composition: 119 mM NaCl, 4.7 mM KCl, 14.9 mM NaHCO 3 , 1.2 mM MgSO 4 ⅐ 7H 2 O, 2.5 mM CaCl 2 , 1.18 mM KH 2 PO 4 , and 5.5 mM glucose at 37°C and gassed with 95% O 2 and 5% CO 2 .…”
Section: Mp Productionmentioning
confidence: 99%
“…The contribution of different macromolecules and signaling events to EC mechanical phenotype is still poorly understood. Previous studies suggested the active role of actin cytoskeleton and regulatory proteins such as myosin light chain kinase in control of cellular stiffness and mechanosensing [22,23]. According to the accomplished measurements, height distribution across EC is heterogeneous: cell center has the maximum thickness (~ 1 μm) due to the presence of nucleus, while the distal regions are significantly thinner (~ 100 nm) (Fig.…”
Section: Resultsmentioning
confidence: 91%